Transnational terrorism and state accountability: a new theory of prevention - Proulx, Vincent-Joël (Hart monographs in transnational and international law, 2012)
Introduction --State responsibility, terrorism and international law --The impact of 9/11 on international law and beyond --Unity through vagueness : the challenges of devising general rules of responsibility --Rethinking the rationale underlying state responsibility for terrorism : trans-substantive rules, domestic analogies and the rationalist agenda --Implementing a two-tiered strict liability-infused model.